1999
DOI: 10.1557/s1092578300003264
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical Etching of InxGa1−xN

Abstract: A comparison of KOH, NaOH and AZ400K solutions for UV photo-assisted etching of undoped and n + GaN is discussed. The etching is diffusion-limited (E a < 6kCal·mol -1 ) under all conditions and is significantly faster with bias applied to the sample during light exposure. No etching of InN was observed, due to the very high n-type background doping (> 10 20 cm -3 ) in the material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…15) In addition, they also result in the fabrication of rough etched sidewalls. Various investigations of wet etching by photo-electrochemical etching [16][17][18][19][20][21] and anodic etching [22][23][24] techniques have been carried out using KOH, H 3 PO 4 , and NaOH solutions. These techniques have advantages in terms of cost, simplicity, and low damage.…”
Section: Introductionmentioning
confidence: 99%
“…15) In addition, they also result in the fabrication of rough etched sidewalls. Various investigations of wet etching by photo-electrochemical etching [16][17][18][19][20][21] and anodic etching [22][23][24] techniques have been carried out using KOH, H 3 PO 4 , and NaOH solutions. These techniques have advantages in terms of cost, simplicity, and low damage.…”
Section: Introductionmentioning
confidence: 99%
“…30 It is generally understood that the wet oxidation rate is limited by the diffusion of OH − ions, as with PEC etching of n-GaN. 25,29,31,32 In our oxidation studies, however, we observed current variation with increasing UV light intensity. This indicated that the oxidation rate is mainly limited by the generation of holes.…”
Section: A Cyclic Voltammetry Measurement and Oxidation Ratementioning
confidence: 66%
“…[6][7][8] Several techniques have also been used for dry etching of GaN layers. [6][7][8] Several techniques have also been used for dry etching of GaN layers.…”
Section: Introductionmentioning
confidence: 99%